Negotiating between the urban landscape and the domestic space: adaptive climates in Ostiense (Rome) - Panella, Giordana (Contesti. Città, territori, progetti, 2026)
Technological rationalization of recent decades has definitively dissociated the management of comfort from its context. The "passivation" and "efficiency" of spaces of everyday life have led to a technological setup capable of altering temperature, lighting, and ventilation to achieve a standard, rather than a perceptive level of comfort. This "techno" functionalism, however, is neither neutral nor democratic. By looking at the consumption patterns in the Mediterranean area, energy consumption increases significantly during the summer due to heat waves and the Urban Heat Island (UHI) effect, caused by impermeable surfaces, limited vegetation, and poor urban ventilation. The widespread use of cooling and ventilation systems leads to high energy demand, with environmental and economic consequences. However, access to these systems is not guaranteed for everyone, especially for those living in energy poverty, renters, or people in precarious housing conditions. Urban policies often prioritize technological models such as Positive Energy Districts and Near Zero Energy Buildings, which are frequently unsuitable for the existing building stock and more accessible in countries with greater investment capacity, thus reinforcing disparities between Northern and Southern Europe. Working with the actual capacity for renewable energy production, energy flexibility, and energy efficiency within given urban contexts is the perspective that interests PEDFORALL, an European research project deeply connected to the specific context of Ostiense, a neighborhood adjacent to the city centre of Rome. Based on the recognition that current energy adaptation strategies have little room to take root in a district such as Ostiense, this contribution proposes a number of strategies for energy transition which are elaborated from the specificities of the site: analyses span from the domestic energy behaviors associated to a low-performing building stock, the quantity and quality presence of vegetation and wet areas, the geographies of paving and building materials, wind strengths and directions. The result of the design exploration offers a possible way to adapt to the changing climatic conditions and to enhance the opportunities to reduce energy use. Like the analyses, the configurations that attempt to spatialise the possibilities of energy-climate resilience work at very different scales, from the domestic space to the street, to the vacant lot, up to the level of the river park crossing the area. They are certainly not ready-made answers, but rather keys to understanding and discussing the adaptability of existing parts of the city.